The roots of Pope Francis' social and political thought : from Argentina to the Vatican - Rourke, Thomas R. (Rowman & Littlefield, 2016)
In The Roots of Pope Francis's Social and Political Thought Thomas R. Rourke traces the development of Pope Francis's thinking from his time as a Jesuit provincial through today. Meticulously researched, the book draws on decades of Francis's writing, much of it unavailable in English, to assess Francis's approach to culture, politics, and society.